THE WRITING STRATEGIES OF AMERICAN UNIVERSITY STUDENTS: FOCUSING ON MEMORY, COMPENSATION, SOCIAL AND AFFECTIVE STRATEGIES - Cabrejas Peñuelas, Ana Belén (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This study examines the self-reported strategy use of a group of 231 American students in their writing tasks. The Inventory of Learning Strategies questionnaire has been created and validated for this study, as well as a background questionnaire. The results indicate that proficient and less proficient writers use a wide variety of strategies; however, expert writers favour the use of cognitive, metacognitive and compensation strategies, followed by affective, memory and social strategies. The established relationships between the frequencies of strategy use and grade in English by means of ANOVA show that writers who get the best grades use more strategies. Women also use more strategies than men in terms of both categories and individual strategies. Finally, the pattern of writing strategies used by writers may be illustrative of their learning style. Resumen Este estudio examina el uso declarado de estrategias de escritura de un grupo de 231 estudiantes americanos. El cuestionario Inventario de Estrategias de Aprendizaje se ha creado y validado para este estudio, así como un cuestionario personal. Los resultados indican que los estudiantes experimentados en expresión escrita y menos experimentados utilizan un amplio numero de estrategias, aunque los estudiantes expertos favorecen el uso de las estrategias cognitivas, metacognitivas y compensatorias, seguidas de las estrategias afectivas, de memoria y sociales. Las relaciones establecidas entre la frecuencia en el uso de estrategias y la nota en ingles por medio de ANOVA indican que los estudiantes que tienen mejores notas hacen un mayor uso de las estrategias. Las mujeres también utilizan más estrategias que los hombres tanto por categorías como por estrategias individuales. El patrón de estrategias de escritura utilizado por los escritores puede ser ilustrativo de su estilo de aprendizaje.